2004
DOI: 10.1291/hypres.27.517
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Candesartan and Amlodipine in a Monkey Atherosclerotic Model

Abstract: Angiotensin II receptor blockers could prevent the development of atherosclerosis beyond reducing blood pressure in monkeys fed a high-cholesterol diet. However, it has been unclear whether hypotensive effects improve atherosclerosis in primates. We investigated whether antihypertensive agents, an angiotensin II receptor antagonist, candesartan, and a calcium channel blocker, amlodipine, prevent areas of atherosclerotic lesions in the aorta of monkeys fed a high-cholesterol diet. Seventeen male monkeys fed a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…They reported that in the ApoEKO mice treated with streptozotocin, the vascular renin-angiotensin system plays a critical role in mediating acceleration of ath- erosclerosis, and this may explain why irbesartan was superior to amlodipine in reducing the diabetes-associated acceleration of atherosclerosis. Takai et al (23) reported that amlodipine tended to decrease the atherosclerotic area in monkeys fed a high-cholesterol diet, although this effect was not statistically significant. In contrast, others have reported that amlodipine inhibited atherosclerosis in non-diabetic animal models of atherosclerosis (24,25).…”
Section: Discussionmentioning
confidence: 97%
“…They reported that in the ApoEKO mice treated with streptozotocin, the vascular renin-angiotensin system plays a critical role in mediating acceleration of ath- erosclerosis, and this may explain why irbesartan was superior to amlodipine in reducing the diabetes-associated acceleration of atherosclerosis. Takai et al (23) reported that amlodipine tended to decrease the atherosclerotic area in monkeys fed a high-cholesterol diet, although this effect was not statistically significant. In contrast, others have reported that amlodipine inhibited atherosclerosis in non-diabetic animal models of atherosclerosis (24,25).…”
Section: Discussionmentioning
confidence: 97%
“…In particular, angiotensin II promotes hypertrophy of cardiovascular cells and aldosterone causes fibrosis of the cardiovascular tissues (12,13). Therefore, antihypertensive drugs that suppress RAAS, such as ARBs and ACE inhibitors, are expected to confer protection against hypertensive injuries in cardiovascular organs that goes beyond their hypotensive effects (32). Fibrosis and deposition of intercellular matrices such as collagen in the cardiac tissue cause reduction in left ventricular distensibility (33).…”
Section: Discussionmentioning
confidence: 99%
“…The AT1 receptor antagonists irbesartan and candesartan but not amlodipine treatment showed beneficial effects in diabetic apolipoprotein E-null mouse or monkeys. [31][32] …”
Section: Liu Et Al Increased Trpc3 In Shrmentioning
confidence: 99%